1 [mu] m ultra-wideband tunable diamagnetic optical fiber doped with composite quantum dots and preparation method of 1 [mu] m ultra-wideband tunable diamagnetic optical fiber
By using ultra-wideband tunable nanocomposites doped with composite quantum dots in the fiber core and combining with anti-magnetic-optical phosphate glass tubes, the problems of insufficient emission wavelength in the near-infrared short-wave region and interference from the external magnetic field are solved, and the ultra-wideband, tunable and anti-magnetic characteristics of the fiber are realized.
Patent Information
- Application Number
- CN202411152853.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art has failed to achieve an effective emission wavelength below 1000 nm in the near-infrared shortwave region, and cannot effectively resist external magnetic field interference.
A 1μm ultra-wideband tunable antimagnetic fiber with doped composite quantum dots is used to form a uniformly distributed ultra-wideband tunable nanocomposite by using silica nanoparticles, InAs quantum dots, Nd3+ compounds and Yb3+ compounds in the fiber core, combined with an antimagnetic phosphate glass tube.
The ultra-wideband and tunable characteristics in the near-infrared short-wave region are realized, and the anti-magnetic properties of the optical fiber are significantly improved, so that it can exhibit uniform and stable anti-magnetic performance under the interference of external magnetic field.
Smart Images

Figure CN119596442A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of optical fibers, and more specifically, to a 1 μm ultra-wideband tunable anti-magnetic optical fiber doped with composite quantum dots and a preparation method thereof. Background Art
[0002] Light is an electromagnetic wave, and optical fiber is a fiber made of glass or plastic that is used as a light transmission tool. Optical fibers are classified according to their working wavelengths into ultraviolet fibers, visible fibers, near-infrared fibers, and infrared fibers. The emission wavelength of the infrared fiber segment is relatively narrow at 1-2μm. Even glass fibers doped with other substances still fail to reach the desired emission wavelength range, and it is difficult to eliminate the interference of external magnetic fields on fiber lasers.
[0003] In the prior art, a Chinese patent with the announcement number CN109437562B discloses a 2μm ultra-wideband tunable luminescent quantum dot-doped rare earth laser glass and its preparation method. The molar percentage composition of the glass is: SiO24~60%; NaCO330~40%; Al2O33~7%; ZnO 5~10%; ZnS 1~4%; PbO 0.5~2%; Tm2O30.05~4%. The present invention is prepared by melt cooling method, and quantum dots are precipitated after heat treatment. The quantum dots in the glass prepared by the present invention are PbS, and the size is 1.7-5.1nm. Under 808nm laser diode pumping, Tm 3+ The ultra-broadband fluorescence of PbS is located in the 2μm band, with an emission wavelength range of 1400-2600nm and a tuning range of up to 1200nm, which is suitable for the preparation and application of 2μm broadband tunable laser glass fibers and fiber lasers.
[0004] The minimum emission wavelength of the above optical fiber is 1400nm, which does not solve the problem of emission wavelength below 1000nm in the near-infrared short-wave region, and there is no detection of the interference of this optical fiber with the external magnetic field. Summary of the invention
[0005] In order to solve the problem of emission wavelength below 1000nm in the near-infrared shortwave region and ensure that the external magnetic field has low interference on the optical fiber, the present application provides a 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots and a preparation method thereof.
[0006] The present application provides a 1μm ultra-wideband tunable anti-magnetic optical fiber doped with composite quantum dots, which adopts the following technical solution: A 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots comprises an antimagnetic optical phosphate glass tube and an ultra-wideband tunable nanocomposite, wherein the antimagnetic optical phosphate glass tube is the fiber tube of the optical fiber, and the ultra-wideband tunable nanocomposite is the fiber core of the optical fiber. The ultra-wideband tunable nanocomposite comprises the following materials in parts by weight: 30-50 parts of silicon dioxide nanoparticles, 10-15 parts of InAs quantum dots, 2-4 parts of succinic anhydride dissolved in N,N-dimethylformamide, 1-3 parts of Tween 80 and 4-8 parts of Nd 3+ Compound, 1-4 parts Yb 3+ The compound was prepared.
[0007] By adopting the above technical solution, the silica nanoparticles account for the largest proportion, and as the core substrate of the ultra-wideband tunable nanocomposite, InAs quantum dots can be connected to the silica nanoparticles, and Nd 3+ Compounds and Yb 3+ Compounds can also be adsorbed on silica nanoparticles, so InAs quantum dots, Nd 3+ Compounds and Yb 3+ The compounds can be evenly located on the surface of silica nanoparticles, so that when the silica is evenly distributed, InAs quantum dots, Nd 3+ Compounds and Yb 3+ The compounds are uniformly distributed in the ultra-broadband tunable nanocomposite; and InAs quantum dots, Nd 3+ Compounds and Yb 3+ The compounds all have emission spectrum characteristics in the near-infrared short-wave region. Under the synergistic effect of the three, the ultra-wideband tunable nanocomposite has a wider emission wavelength range in the near-infrared short-wave region and a larger tunable range. The ultra-wideband tunable nanocomposite is used in the core of the optical fiber and is integrally formed with the anti-magnetic phosphate glass tube of the optical fiber tube at high temperature. The prepared optical fiber also has ultra-wideband and tunable characteristics in the near-infrared short-wave region. The anti-magnetic optical glass tube itself has anti-magnetic properties, and the main component of the ultra-wideband tunable nanocomposite, silicon dioxide, also has anti-magnetic properties. The silicon dioxide in this application can not only be used as InAs quantum dots, Nd 3+ Compounds and Yb 3+ The core substrate of the compound can combine its own advantages of strong chemical stability, strong hardness, and strong magnetism, and cooperate with the anti-magnetic glass tube to improve the anti-magnetic properties of the optical fiber from the inside to the surface. The optical fiber composition and structure of the present application make the optical fiber of the present application have uniform and strong anti-magnetic optical performance.
[0008] Optionally, the InAs quantum dots are amino-modified InAs quantum dots.
[0009] By adopting the above technical scheme, succinic anhydride dissolved in N,N-dimethylformamide can connect to silica nanoparticles, and amino-modified InAs quantum dots can connect to the carboxyl group of succinic anhydride through the amino group to form an amide group, so that the InAs quantum dots are firmly connected to the silica nanoparticles. In the later stage, part of the silica in the ultra-wideband tunable composite is melt-connected to the antimagnetic phosphate glass tube at high temperature, and it is difficult to affect the distribution uniformity and stability of the InAs quantum dots in the optical fiber.
[0010] Optionally, the particle size of the InAs quantum dots is 15-30 nm.
[0011] By adopting the above technical solution, since the surface of InAs quantum dots is connected to amino groups, the particle size range of InAs quantum dots is 15-30nm. InAs quantum dots in this particle size range can establish chemical bonds with the surface of silica nanoparticles while ensuring uniform attachment to the surface of silica nanoparticles.
[0012] Optionally, the silica nanoparticles have a particle size of 85-95 nm.
[0013] By adopting the above technical solution, the 85-95nm silica nanoparticles are exactly 3-6 times the particle size of InAs quantum dots. When the amount of silica nanoparticles and InAs quantum dots added is reasonable, it can ensure that the surface of silica nanoparticles is evenly connected to InAs quantum dots, and InAs quantum dots will not gather on certain silica nanoparticles in large quantities, and there are very few silica nanoparticles that are not connected to InAs quantum dots; thus ensuring the uniformity of silica nanoparticles, InAs quantum dots, and Nd 3+ Compounds and Yb 3+ If the compound can be evenly distributed, the optical fiber's spectral emission and anti-magnetic stability will be higher.
[0014] Optionally, the Nd 3+ Compounds using nano Nd2O3; Yb 3+ The compound uses nano Yb2O3.
[0015] By adopting the above technical solution, nano-Nd2O3 and nano-Yb2O3 are both rare earth elements with relatively stable chemical properties, and only oxygen atoms are introduced into the ultra-wideband tunable nano-composite. Oxygen atoms themselves are also components of the anti-magnetic phosphate glass tube. No other atoms are introduced, thus ensuring the stability of the optical fiber properties and functions.
[0016] Optionally, the particle size of the nano Nd2O3 is 20-30nm; the particle size of the nano Yb2O3 is 20-30nm.
[0017] By adopting the above technical solution, nano Nd2O3 and nano Yb2O3 with a particle size of 20-30nm, when the amount of silicon dioxide nanoparticles and InAs quantum dots added is reasonable, it can ensure that the surface of silicon dioxide nanoparticles is evenly connected with InAs quantum dots and Nd 3+ Compounds and Yb 3+ Compounds, InAs quantum dots, Nd 3+ Compounds and Yb 3+ The compounds will not gather on certain silica nanoparticles in large quantities, and there are very few silica nanoparticles that are not connected to InAs quantum dots; this ensures that the silica nanoparticles, InAs quantum dots, and Nd 3+ Compounds and Yb 3+ If the compound can be evenly distributed, the optical fiber's spectral emission and anti-magnetic stability will be higher.
[0018] Optionally, the composition of the anti-magnetic phosphate glass tube is P2O5-Al2O3-K2O-BaO-B2O3-La2O3-Yb2O3.
[0019] By adopting the above technical solution, the anti-magneto-optical phosphate glass tube with La2O3 and Yb2O3 added has stronger anti-magneto-optical performance, which cooperates with the silica in the ultra-wideband tunable nanocomposite to further improve the anti-magneto-optical performance of the optical fiber.
[0020] In a second aspect, the present application provides a method for preparing a 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots, using the following technical solution.
[0021] The invention discloses a method for preparing a 1μm ultra-wideband tunable anti-magnetic optical fiber doped with composite quantum dots. The method comprises the following steps: weighing anti-magnetic optical silicate glass raw materials according to the composition raw materials of P2O5-Al2O3-K2O-BaO-B2O3-La2O3-Yb2O3, stirring to melt under N2 conditions of 800-1000°C, pouring into a preheated rotary furnace and rotating for 1-2 minutes, taking out an anti-magnetic optical phosphate glass tube after cooling, further preheating the anti-magnetic optical glass tube, then melting an ultra-wideband tunable nanocomposite under N2 conditions of 950-1050°C for 40-50 minutes, pouring into the anti-magnetic optical phosphate glass tube to obtain an optical fiber original rod, drawing the optical fiber original rod in an optical fiber tower at a temperature of 600-650°C, and annealing at 280-300°C for 3-5 hours to obtain a 1μm ultra-wideband tunable anti-magnetic optical fiber doped with composite quantum dots.
[0022] By adopting the above technical scheme and the above method to prepare the optical fiber, in the N2 atmosphere and under the high temperature condition, the raw materials are unlikely to have other side reactions, and the anti-magnetic phosphate glass raw materials can form a high-purity anti-magnetic phosphate glass tube; the silicon dioxide nanoparticles in the ultra-wideband tunable nanocomposite can also partially melt and combine with the anti-magnetic phosphate glass tube under the above conditions while retaining their own structure; because the phosphate glass can dissolve rare earth ions, part of the Nd 3+ Compounds and Yb 3+ The compound can be melted by the inner wall of the antimagnetic phosphate glass tube, and due to Nd 3+ Compounds and Yb 3+ The compound itself has anti-magnetic-optical properties. The preparation method of the present application enables the ultra-wideband tunable nanocomposite and the anti-magnetic-optical phosphate glass tube to be integrally formed. The prepared optical fiber has ultra-wideband and tunable characteristics in the near-infrared short-wave region, and the overall anti-magnetic-optical performance is uniform and stable.
[0023] Optionally, the preparation method of the ultra-wideband tunable nanocomposite includes the following steps: uniformly mixing silica nanoparticles, Nd2O3, Yb2O3 and water, stirring at a speed of 1000-1500rpm for 24 hours to obtain a nanocomposite precursor; uniformly mixing the nanocomposite precursor, succinic anhydride dissolved in N,N-dimethylformamide, cyclohexane, Tween 80 and InAs quantum dots, stirring at a speed of 1000-1500rpm for 24 hours, then centrifuging to remove the supernatant, washing three times to remove impurities, and obtaining an ultra-wideband tunable nanocomposite.
[0024] By adopting the above technical scheme, the purpose of first mixing silica nanoparticles, Nd2O3, Yb2O3 and water is that Nd2O3 and Yb2O3 are insoluble in water, and Nd2O3 and Yb2O3 will aggregate and attach to the silica nanoparticles; the silica nanoparticles form stable hydroxyl groups on the surface in water, and after the succinic anhydride dissolved in N,N-dimethylformamide opens the ring, the carboxyl group at one end can be connected to the silica nanoparticles, and the other end can be connected to the InAs quantum dots carrying amino groups, so that the InAs quantum dots and the silica nanoparticles have a long chain connection, which will not affect the connection between Nd2O3, Yb2O3 and the silica nanoparticles; cyclohexane is a solvent for subsequent reactions and is easy to remove, and Tween 80 is an emulsifier, which can well fuse the reaction raw materials together to facilitate the reaction; and finally, silica nanoparticles tightly coated with InAs quantum dots, Nd2O3 and Yb2O3 are formed.
[0025] Optionally, the washing solution used in the washing step is chloroform.
[0026] By adopting the above technical solution, chloroform as a washing liquid can not only be mutually soluble with cyclohexane, but also be extremely volatile. Therefore, using chloroform as a solvent can obtain a purer ultra-wideband tunable nanocomposite.
[0027] In summary, this application has the following beneficial effects: 1. In this application, InAs quantum dots, Nd 3+ Compounds and Yb 3+ The compounds all have emission spectrum characteristics in the near-infrared short-wave region. Under the synergistic effect of the three, the ultra-wideband tunable nanocomposite has a wider emission wavelength range in the near-infrared short-wave region and a larger tunable range. The ultra-wideband tunable nanocomposite is used in the core of the optical fiber and is integrally formed with the anti-magnetic phosphate glass tube of the optical fiber tube at high temperature. The prepared optical fiber also has ultra-wideband and tunable characteristics in the near-infrared short-wave region. 2. In the present application, the silica nanoparticles in the ultra-wideband tunable nanocomposite are partially melt-bonded with the anti-magnetic phosphate glass tube, which can combine its own advantages of strong chemical stability, strong hardness, and strong magnetism while retaining its own structure, and cooperate with the anti-magnetic glass tube to improve the anti-magnetic property of the optical fiber from the inside to the surface, so that the overall anti-magnetic property of the prepared optical fiber is uniform and stable; 3. In this application, some Nd 3+ Compounds and Yb 3+ The compound can be melted by the inner wall of the anti-magnetic phosphate glass tube, so that the ultra-wideband tunable nano-composite and the anti-magnetic phosphate glass tube are integrally formed, and the prepared optical fiber has stable ultra-wideband and tunable characteristics in the near-infrared short-wave region. DETAILED DESCRIPTION
[0028] Figure 1 Aims to demonstrate the XPS spectra of ultra-broadband tunable nanocomposites; Figure 2 Schematic diagram of the morphology of the nanocomposite designed to demonstrate ultra-broadband tunable properties; Figure 3 The purpose is to show the luminescence spectrum comparison of the optical fibers of Examples 1, 2, 3, 4, 5, and 6 and Comparative Examples 2, 3, 4, and 5; Figure 4 The purpose is to show the anti-magnetic comparison diagram of the optical fiber of Examples 3, 6 and Comparative Example 1.
[0029] The raw materials of the examples and comparative examples of the present application can all be purchased commercially; Succinic anhydride dissolved in N,N-dimethylformamide, the concentration of succinic anhydride is 0.5 g / mL; InAs quantum dots and PbS quantum dots were purchased from Xi'an Qiyue Biotechnology Co., Ltd.; Peroxide nanospheres and Au nanoparticles were purchased from Zhongke Leiming Technology Co., Ltd.; Nd2O3, Nd2Cl3, purchased from Xi'an Qiyue Biotechnology Co., Ltd.; Yb2O3 and Yb2Cl3 were purchased from Zhongnuo New Materials Technology Co., Ltd.; The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0030] Ultra-wideband tunable nanocomposite XPS element detection method: Instrument name, X-ray diffractometer; Model, Shimadzu D8ADVANCE; Ray, Al-Kα ray.
[0031] Optical fiber luminescence spectrum detection method: Use 808nm high-power FP pump laser diode, power: 200mW. Example
[0032] Optical fiber antimagnetic detection method: Instrument name, magnetic measurement system; Model, Quantum Design MPMS3. Example Example 1
[0033] A 1 μm ultra-wideband tunable anti-magnetic optical fiber doped with composite quantum dots, the preparation method comprising the following steps: Preparation of ultra-broadband tunable nanocomposites: Step 1, 30 g of silica nanoparticles with a particle size of 85-95 nm, 4 g of Nd2O3 with a particle size of 20-30 nm, 4 g of Yb2O3 with a particle size of 20-30 nm and water are mixed evenly, stirred at a speed of 1500 rpm for 24 hours, and then centrifuged at a speed of 1500 rpm for 5 minutes, and the supernatant is removed to obtain a nanocomposite precursor; Step 2, mixing the nanocomposite precursor, 2 g of succinic anhydride dissolved in N,N-dimethylformamide, 30 mL of cyclohexane, and 3 g of Tween 80, stirring at a speed of 1000 rpm for 12 h to obtain a carboxyl nanocomposite precursor solution, and centrifuging the carboxyl nanocomposite precursor solution at a speed of 1500 rpm for 10 min to obtain a carboxyl nanocomposite; Step 3, mix the carboxyl nanocomposite, 40 mL of cyclohexane and 15 g of InAs quantum dots with a particle size of 15-30 nm, stir at 1000 rpm for 24 hours, then centrifuge at 1500 rpm for 15 minutes, remove the supernatant to obtain a precipitate, and wash the precipitate three times. The specific washing steps are: use chloroform to dissolve the precipitate at a volume ratio of 5:1, then centrifuge at 1500 rpm for 15 minutes, and remove the supernatant; obtain an ultra-wideband tunable nanocomposite. Example
[0034] Preparation of 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots: Step a, weighing anti-magnetic optical silicate glass raw materials according to the composition raw materials of P2O5-Al2O3-K2O-BaO-B2O3-La2O3-Yb2O3, stirring until melting under N2 conditions at 800°C, pouring into a preheated rotary furnace and rotating at a speed of 800r / min for 2min, taking out the anti-magnetic optical phosphate glass tube after cooling, fixing the anti-magnetic optical glass tube in a U-shaped mold, and continuing to preheat at 200°C; Step b, melting the ultra-wideband tunable nanocomposite at 1050° C. for 40 min, pouring it into an anti-magnetic phosphate glass tube, and annealing it at 300° C. for 3 h to obtain an optical fiber raw rod; Step c, loading the fiber rod into the feed port of the fiber tower, and drawing the fiber in the fiber tower at a temperature of 650°C; setting the upper nitrogen pipe N2 flow rate to 75cm 3 / min, N2 flow rate in lower nitrogen pipe 5cm 3 / min, the preform rod descending speed is 0.9mm / min, the fiber winding drum speed is 6.0r / min, and the optical fiber is annealed at 350℃ for 4h after drawing to obtain a 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots. Example 2 Example
[0035] The difference from Example 1 is that the amount of raw materials used in preparing the ultra-wideband tunable nanocomposite is different. The specific steps are as follows: Preparation of ultra-broadband tunable nanocomposites: Step 1, 50 g of silica nanoparticles with a particle size of 85-95 nm, 8 g of Nd2O3 with a particle size of 20-30 nm, 1 g of Yb2O3 with a particle size of 20-30 nm and water are mixed evenly, stirred at a speed of 1500 rpm for 24 hours, and then centrifuged at a speed of 1500 rpm for 5 minutes, and the supernatant is removed to obtain a nanocomposite precursor; Step 2, mixing the nanocomposite precursor, 4 g of succinic anhydride dissolved in N,N-dimethylformamide, 30 mL of cyclohexane, and 1 g of Tween 80, stirring at a speed of 1000 rpm for 12 h to obtain a carboxyl nanocomposite precursor solution, and centrifuging the carboxyl nanocomposite precursor solution at a speed of 1500 rpm for 10 min to obtain a carboxyl nanocomposite; Step 3, mix the carboxyl nanocomposite, 40 mL of cyclohexane and 10 g of InAs quantum dots with a particle size of 15-30 nm, stir at 1000 rpm for 24 hours, then centrifuge at 1500 rpm for 15 minutes, remove the supernatant to obtain a precipitate, and wash the precipitate three times. The specific washing steps are: use chloroform to dissolve the precipitate at a volume ratio of 5:1, then centrifuge at 1500 rpm for 15 minutes, and remove the supernatant; obtain an ultra-wideband tunable nanocomposite. Example 3 Example
[0036] The difference from Example 1 is that the amount of raw materials used in preparing the ultra-wideband tunable nanocomposite is different. The specific steps are as follows: Preparation of ultra-broadband tunable nanocomposites: Step 1, 40 g of silica nanoparticles with a particle size of 85-95 nm, 6 g of Nd2O3 with a particle size of 20-30 nm, 2.5 g of Yb2O3 with a particle size of 20-30 nm and water are mixed evenly, stirred at a speed of 1500 rpm for 24 hours, and then centrifuged at a speed of 1500 rpm for 5 minutes, and the supernatant is removed to obtain a nanocomposite precursor; Step 2, mixing the nanocomposite precursor, 3 g of succinic anhydride dissolved in N,N-dimethylformamide, 30 mL of cyclohexane, and 2 g of Tween 80, stirring at a speed of 1000 rpm for 12 h to obtain a carboxyl nanocomposite precursor solution, and centrifuging the carboxyl nanocomposite precursor solution at a speed of 1500 rpm for 10 min to obtain a carboxyl nanocomposite; Step 3, mix the carboxyl nanocomposite, 40 mL of cyclohexane and 12 g of InAs quantum dots with a particle size of 15-30 nm, stir at 1000 rpm for 24 hours, then centrifuge at 1500 rpm for 15 minutes, remove the supernatant to obtain a precipitate, and wash the precipitate three times. The specific washing steps are: use chloroform to dissolve the precipitate at a volume ratio of 5:1, then centrifuge at 1500 rpm for 15 minutes, and remove the supernatant; obtain an ultra-wideband tunable nanocomposite. Example 4 Example
[0037] The difference from Example 3 is that the particle sizes of silica nanoparticles, Nd2O3, Yb2O3, and InAs quantum dots are different; the particle size of silica nanoparticles is 100-120nm, the particle size of Nd2O3 is 40-50nm, the particle size of Yb2O3 is 40-50nm, and the particle size of InAs quantum dots is 40-50nm. Example 5 Example
[0038] The difference from Example 3 is that the particle sizes of silica nanoparticles, Nd2O3, Yb2O3, and InAs quantum dots are different; the particle size of silica nanoparticles is 40-50nm, the particle size of Nd2O3 is 10-15nm, the particle size of Yb2O3 is 10-15nm, and the particle size of InAs quantum dots is 10-15nm. Example 6
[0039] The difference from Example 3 is that an equal weight of Nd2Cl3 is used instead of Nd2O3, and an equal weight of Yb2Cl3 is used instead of Yb2O3.
[0040] Comparative Example 1 The difference from Example 3 is that an equal weight of gold nanoparticles is used instead of silicon dioxide nanoparticles, the particle size of the gold nanoparticles is 85-95 nm, and the gold nanoparticles are PEG-gold nanoparticles carrying hydroxyl groups on the surface.
[0041] Comparative Example 2 The difference from Example 3 is that the InAs quantum dots in step 2 are replaced by PbS quantum dots of equal weight.
[0042] Comparative Example 3 The difference from Example 3 is that Nd2O3 and Yb2O3 in step 1 are replaced by Eu2O3 of equal total weight, and the weight of Eu2O3 is 8.5 g; the specific steps of step 1 are as follows: Step 1, 40g of silica nanoparticles with a particle size of 85-95nm, 8.5g of Eu2O3 with a particle size of 20-30nm and water are mixed evenly, stirred at a speed of 1500rpm for 24h, and then centrifuged at a speed of 1500rpm for 5min, and the supernatant is removed to obtain a nanocomposite precursor.
[0043] Comparative Example 4 The difference from Example 3 is that Nd2O3 and Yb2O3 in step 3 are replaced by InAs quantum dots with the same total weight. The specific steps of step 1 are as follows: Step 1, 40 g of silica nanoparticles with a particle size of 85-95 nm, 8.5 g of InAs quantum dots and water are mixed evenly, stirred at a speed of 1500 rpm for 24 hours, and then centrifuged at a speed of 1500 rpm for 5 minutes, and the supernatant is removed to obtain a nanocomposite precursor.
[0044] Comparative Example 5 The difference from Example 3 is that the InAs quantum dots in step 3 are replaced with Nd2O3 and Yb2O3 of equal total weight. The specific steps of step 3 are as follows: Step 3, mix the carboxyl nanocomposite, 40 mL of cyclohexane and 12 g of Nd2O3 and Yb2O3 with a particle size of 20-30 nm, wherein the weight ratio of Nd2O3 to Yb2O3 is 3:1, stir at 1000 rpm for 24 hours, then centrifuge at 1500 rpm for 15 minutes, remove the supernatant to obtain a precipitate, wash the precipitate three times, and the specific washing steps are: use chloroform to dissolve the precipitate in a volume ratio of 5:1, then centrifuge at 1500 rpm for 15 minutes, and remove the supernatant; obtain an ultra-wideband tunable nanocomposite.
[0045] Comparative Example 6 The difference from Example 3 is that the step a in the preparation process of the 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots is different, and antimagnetic optical silicate glass raw material is used. The specific steps are as follows: Preparation of 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots: Step a, weighing anti-magnetic silicate glass raw materials according to the composition raw materials of 70Si2O5-1Al2O3-0.8CaO-7.9NaO-15.8K2O-5B2O3-0.1La2O3-0.1Yb2O3, stirring until melting under N2 conditions at 1200°C, pouring into a preheated rotary furnace and rotating at a speed of 800r / min for 2min, taking out the anti-magnetic silicate glass tube after cooling, fixing the anti-magnetic glass tube in a U-shaped mold, and continuing to preheat at 400°C; Step b, melting the ultra-wideband tunable nanocomposite at 1050° C. for 40 min, pouring it into an anti-magnetic phosphate glass tube, and annealing it at 300° C. for 3 h to obtain an optical fiber raw rod; Step c, loading the fiber rod into the feed port of the fiber tower, and drawing the fiber in the fiber tower at a temperature of 850°C; setting the upper nitrogen pipe N2 flow rate to 75cm 3 / min, N2 flow rate in lower nitrogen pipe 5cm 3 / min, the preform rod descending speed is 0.9mm / min, the fiber winding drum speed is 6.0r / min, and the optical fiber is annealed at 350℃ for 4h after drawing to obtain a 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots.
[0046] Combination Figure 1 It can be seen that Figure 1 This is the XPS spectrum of the ultra-wideband tunable nanocomposite prepared in Example 3 of the present application. The data in the spectrum confirm that the ultra-wideband tunable nanocomposite contains elements such as C, O, Si, As, In, Yb, and Nd, indicating that the preparation method of the ultra-wideband tunable nanocomposite of the present application does connect InAs quantum dots, Nd2O3 and Yb2O3 to the surface of silica nanoparticles.
[0047] Combination Figure 2 It can be seen that Figure 2 Schematic diagram of the structure of the ultra-wideband tunable nanocomposite prepared in Example 3 of the present application, and Figure 1 Combined with the detection results, it is proved that the preparation method of the ultra-wideband tunable nanocomposite in the present application does connect InAs quantum dots, Nd2O3 and Yb2O3 to the surface of silica nanoparticles.
[0048] Combination Figure 3 It can be seen that Figure 3 The luminescence spectrum comparison diagram of the 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots prepared in Examples 1, 2, 3, 4, and 6 of the present application and Comparative Examples 2, 3, 4, and 5 is shown. In the comparison of the luminescence spectrum of the optical fiber of Examples 1, 2, 3, 4, and 5, the luminescence spectrum line of Example 3 has only one peak, no impurity peak, and the luminescence range is 800nm-1200nm, and the tunable range is 400nm. The peaks of the luminescence spectrum lines of Examples 1, 2, 4, and 5 all have two peaks, one large and one small, which proves that the purity of the optical fiber of Examples 1, 2, 4, and 5 is lower than that of the optical fiber of Example 3. The optical fibers of Examples 1, 2, 4, and 5 contain a large amount of impurities. It is inferred that the dosage of the raw materials of the ultra-wideband tunable nano-composites in Examples 1 and 2 is unreasonable, and the excess raw materials are not removed in the end, resulting in more impurities in Examples 1 and 2. The particle size of the raw materials of the ultra-wideband tunable nano-composites in Examples 4 and 5 is unreasonable, and the perfect structure of InAs quantum dots, Nd2O3 and Yb2O3 connected to the surface of the silica nanoparticles is not formed, and there are many impurities; among the raw material dosages for preparing the ultra-wideband tunable nano-composites in this application, Example 3 is the optimal dosage; the raw material particle size range of Example 3 is the best.
[0049] The difference between Example 6 and Example 3 is that in Example 6, Nd2O3 and Yb2O3 are replaced by Nd2Cl3 and Yb2Cl3, and Cl impurities are introduced. Therefore, there are impurity peaks in the luminescence spectrum of the optical fiber prepared in Example 6, which proves that the present invention replaces Nd 3+ , Yb 3+ Nd2O3 and Yb2O3 must be used for introduction.
[0050] The difference between Comparative Examples 2 and 3 and Example 3 is that Comparative Example 2 replaces InAs quantum dots with PbS quantum dots, and Comparative Example 3 replaces Nd2O3 and Yb2O3 with Eu2O3. Therefore, the luminescence spectra of the optical fibers prepared in Comparative Examples 2 and 3 are shifted compared to the luminescence spectra of Example 3, proving that by replacing the type of quantum dots or the type of rare earth metal oxides, the quantum dots cannot cooperate with the rare earth metal oxides to adjust the luminescence range of the optical fiber required by the present application. Therefore, the InAs quantum dots of the present application are the best type of quantum dots, and Nd2O3 and Yb2O3 are the best types of rare earth metal oxides.
[0051] The difference between Comparative Examples 4 and 5 and Example 3 is that in Comparative Example 4, all Nd2O3 and Yb2O3 are replaced with InAs quantum dots, and in Comparative Example 5, all InAs quantum dots are replaced with Nd2O3 and Yb2O3. Therefore, the luminescence spectra of the optical fibers prepared in Comparative Examples 2 and 3 are shifted compared with the luminescence spectra of Example 3, proving that Nd2O3, Yb2O3 and InAs quantum dots cannot replace each other, and Nd2O3, Yb2O3 and InAs quantum dots must be used together as raw materials to give play to the synergistic effect of Nd2O3, Yb2O3 and InAs quantum dots in order to prepare optical fibers with a luminescence spectrum range of 800nm-1200nm.
[0052] Combination Figure 4 It can be seen that Figure 4 This is a comparison chart of the anti-magnetic-optical properties of the optical fibers of Example 3, Comparative Example 1, and Comparative Example 6 of the present application. Compared with Comparative Example 1 and Comparative Example 6, the optical fiber prepared in Example 3 of the present application has a smaller Faraday rotation angle under the condition of the same magnetic induction intensity, which proves that the optical fiber prepared in Example 3 has the best anti-magnetic properties.
[0053] The difference between Comparative Example 1 and Comparative Example 3 is that Comparative Example 1 uses Au nanoparticles to replace silica nanoparticles, and the silica nanoparticles of the present application can cooperate with the anti-magnetic-optical phosphate glass tube to increase the anti-magnetic-optical performance of the fiber. Therefore, the silica nanoparticles of the present application are irreplaceable.
[0054] The difference between Comparative Example 6 and Comparative Example 3 is that Comparative Example 6 uses an anti-magnetic silicate glass tube, and the synergistic effect between the anti-magnetic silicate glass tube and the silica nanoparticles is not as good as that of the anti-magnetic phosphate glass tube. Therefore, the anti-magnetic phosphate glass tube of the present application is irreplaceable. This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots, characterized in that: The invention comprises an anti-magnetic phosphate glass tube and an ultra-wideband tunable nanocomposite, wherein the anti-magnetic phosphate glass tube is the fiber tube of the optical fiber, the ultra-wideband tunable nanocomposite is the fiber core of the optical fiber, and the ultra-wideband tunable nanocomposite comprises the following substances in parts by weight: 30-50 parts of silicon dioxide nanoparticles, 10-15 parts of InAs quantum dots, 2-4 parts of succinic anhydride dissolved in N,N-dimethylformamide, 1-3 parts of Tween 80, 4-8 parts of Nd 3+ Compound and 1-4 parts of Yb 3+ The compound was prepared.
2. The 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 1, characterized in that: The InAs quantum dots are amino-modified InAs quantum dots.
3. The 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 1, characterized in that: The particle size of the InAs quantum dots is 15-30 nm.
4. The 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 1, characterized in that: The particle size of the silicon dioxide nanoparticles is 85-95 nm.
5. The 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 1, characterized in that: The Nd 3+ Compounds using nano Nd2O3; Yb 3+ The compound uses nano Yb2O3.
6. The 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 5, characterized in that: The particle size of the nano Nd2O3 is 20-30nm; the particle size of the nano Yb2O3 is 20-30nm.
7. The 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 1, characterized in that: The composition of the anti-magnetic phosphate glass tube is P2O5-Al2O3-K2O-BaO-B2O3-La2O3-Yb2O3.
8. A method for preparing a 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Antimagnetic phosphate glass raw materials are weighed according to the composition raw materials of P2O5-Al2O3-K2O-BaO-B2O3-La2O3-Yb2O3, stirred until melted under N2 conditions at 800-1000°C, poured into a preheated rotary furnace and rotated for 1-2 minutes, and the antimagnetic phosphate glass tube is taken out after cooling, and the antimagnetic phosphate glass tube is further preheated, and then an ultra-wideband tunable nano-composite is melted at 950-1050°C for 40-50 minutes, and poured into the antimagnetic phosphate glass tube to obtain an optical fiber rod, and the optical fiber rod is drawn at a temperature of 600-650°C in an optical fiber tower, and annealed at 280-300°C for 3-5 hours to obtain a 1μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots.
9. The 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 8, characterized in that: The preparation method of the ultra-wideband tunable nanocomposite comprises the following steps: uniformly mixing silica nanoparticles, Nd2O3, Yb2O3 and water, stirring at a speed of 1000-1500rpm for 24h to obtain a nanocomposite precursor; uniformly mixing the nanocomposite precursor, succinic anhydride dissolved in N,N-dimethylformamide, cyclohexane, Tween 80 and InAs quantum dots, stirring at a speed of 1000-1500rpm for 24h, then centrifuging to remove the supernatant, washing three times to remove impurities, and obtaining an ultra-wideband tunable nanocomposite.
10. The method for preparing a 1 μm ultra-wideband tunable antimagnetic optical fiber doped with composite quantum dots according to claim 9, characterized in that: The washing solution used in the washing step is chloroform.
Citation Information
Patent Citations
A rare-earth-doped laser glass with 2 μm ultrawideband tunable luminescent quantum dots and its preparation method
CN109437562B